Strategic inattention in product search - Adrian Hillenbrand; Svenja Hippel (Max Planck Institute for Research on Collective Goods, 2017)
Online platforms provide search tools that help consumers to get betterfitting product offers. But this technology makes consumer search behavior also easily traceable for the platform and allows for real-time price discrimination. Consumers face a trade-off: Search intensely and receive better fits at potentially higher prices or restrict search behavior - be strategically inattentive - and receive a worse fit, but maybe a better deal. We study the strategic buyer-seller interaction in such a situation theoretically as well as experimentally. The search technology we use in the laboratory leads by construction to better-fitting products, but we indeed find that only sellers profit from the buyers' use of the offered search tools.
Keywords: D11; D42; D82; D83; L11; 330; strategic inattention; price discrimination; information transmission; consumer choice; experiment